2001
DOI: 10.1128/aac.45.1.44-47.2001
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin Inhibits NF-κB Activation in Human Peripheral Blood Mononuclear Cells and Pulmonary Epithelial Cells

Abstract: Macrolide antibiotics modulate the production of proinflammatory cytokines in vivo and in vitro. Transcription of the genes for these proinflammatory cytokines is regulated by nuclear factor B (NF-B). We examined whether or not clarithromycin inhibits the activation of NF-B induced by tumor necrosis factor alpha (TNF- Proinflammatory cytokines are important mediators in inflammation. Macrolide antibiotics exert anti-inflammatory effects through inhibition of the production of proinflammatory cytokines (25,28,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 43 publications
3
78
1
3
Order By: Relevance
“…On the other hand, it was reported that macrolides directly act on monocytes or macrophages and inhibit the production of inflammatory cytokines such as IL-1, IL-8 and TNF-α in vitro [39,40]. It was also reported that macrolides, including erythromycin, inhibit NF-κB activation in mononuclear cells and macrophages [41][42][43]. Kikuchi and colleagues [44] reported that clarithromycin suppressed lipopolysaccharide-induced IL-8 production in human peripheral monocytes and in the human monocytic leukaemia cell line THP-1, through suppression of activator protein-1, and NF-κB transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was reported that macrolides directly act on monocytes or macrophages and inhibit the production of inflammatory cytokines such as IL-1, IL-8 and TNF-α in vitro [39,40]. It was also reported that macrolides, including erythromycin, inhibit NF-κB activation in mononuclear cells and macrophages [41][42][43]. Kikuchi and colleagues [44] reported that clarithromycin suppressed lipopolysaccharide-induced IL-8 production in human peripheral monocytes and in the human monocytic leukaemia cell line THP-1, through suppression of activator protein-1, and NF-κB transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, CM pretreatment was found to suppress IL-1b induced nuclear factor (NF)-kB activity in bronchial epithelial cells, but had no effect on NF-kB activity in the absence of IL-1b stimulation [13]. Since the ability of macrolides to inhibit the secretion of pro-inflammatory cytokine is mediated by inhibition of NF-kB [27], CM may have no effect on the constitutive expression of ICAM-1 and pro-inflammatory cytokines, which may not be associated with NF-kB activation [18]. However, further experiments are required to clarify this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these antibiotics also inhibit the production of prostaglandin E2, and neutrophil chemotaxis and elastase activity. Clarithromycin modulates the proliferation of antigen-specific T cells and enhances the anti-M. avium activity mediated by IL-12 (Ichiyama et al, 2001).…”
Section: Discussionmentioning
confidence: 99%